Measuring the indirect costs associated with the establishment of a wind farm: An application of the contingent valuation method - du Preez, Mario; Menzies, Greig; Sale, Michael; Hosking, Stephen (Journal of Energy in Southern Africa, 2017)
Although a green energy source, the location of electrical generating wind turbines may cause a disamenity effect (negative externality). The establishment of a wind farm is known as a locally undesirable land use (LULU) and leads to the not in my backyard syndrome (NIMBY). In an application of the contingent valuation method (a survey technique which elicits individuals’ preferences and measures these preferences in monetary terms) a willingness to accept a framework was used to estimate the aggregate annual compensation required to allow the construction of a wind farm near Jeffrey’s Bay, South Africa. This compensation amounted to R490 695. A binary choice Logit analysis found that retirement status, concern about climate change, concern about view shed impacts and the offer amount are important predictors of voting for or against the project.